2014
DOI: 10.3102/0162373713507480
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Cognitive Tutor Algebra I at Scale

Abstract: This article examines the effectiveness of a technology-based algebra curriculum in a wide variety of middle schools and high schools in seven states. Participating schools were matched into similar pairs and randomly assigned to either continue with the current algebra curriculum for 2 years or to adopt Cognitive Tutor Algebra I (CTAI), which uses a personalized, mastery-learning, blendedlearning approach. Schools assigned to implement CTAI did so under conditions similar to schools that independently adopt i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(67 citation statements)
references
References 14 publications
(14 reference statements)
0
62
0
1
Order By: Relevance
“…In light of such reasoning, several funding agencies, including the National Science Foundation, the Institute for Educational Sci ences, and the National Institutes for Health, have been engaged in funding research that has been demonstrated to work in more limited contexts in order to determine whether the results can be replicated on a broader scale (e.g., http://www.nsf.gov/pubs/2002/ nsf02062/nsf02062.pdf). Their support has funded research by several teams (e.g., Clements, 2005;Francis, 2011;Fuchs, 2004;Hurtig, 2004;Pane, 2007;Starkey, 2004) as well as the present study.…”
Section: Scaling Up Educational Interventionsmentioning
confidence: 97%
“…In light of such reasoning, several funding agencies, including the National Science Foundation, the Institute for Educational Sci ences, and the National Institutes for Health, have been engaged in funding research that has been demonstrated to work in more limited contexts in order to determine whether the results can be replicated on a broader scale (e.g., http://www.nsf.gov/pubs/2002/ nsf02062/nsf02062.pdf). Their support has funded research by several teams (e.g., Clements, 2005;Francis, 2011;Fuchs, 2004;Hurtig, 2004;Pane, 2007;Starkey, 2004) as well as the present study.…”
Section: Scaling Up Educational Interventionsmentioning
confidence: 97%
“…Results such as these have been critical to the design and continual improvement of the "Cognitive Tutor Algebra" course, now in use by some 600,000 middle and high school students a year. The most recent of many full--year randomized field trials involved 147 schools and showed students using the "Cognitive Tutor Algebra" course learned twice as much as students in traditional algebra courses [9].…”
Section: Cognitive Task Analysis Based On Quantitative Analysis Of Edmentioning
confidence: 99%
“…They are commonly understood as predictions of y C as a function of x (e.g. Pane et al, 2013). In fact, much of the intuition behind prognostic scores supports our use ofŷ C (x) here, though the prognostic score theory will not play a direct role in our argument.…”
Section: Matching In Observational Studies: Reviewmentioning
confidence: 67%